IMPROVING THE STUDENTS’ PRONUNCIATION SKILL THROUGH CHORAL DRILL TECHNIQUE - noening poejilestari (STIBA IEC JAKARTA, 2017)
The aim of this research is to solve the English pronunciation problem. Besides, this research is also to know the effectiveness of using choral drill technique in teaching pronunciation. The research is conducted at SMK Karya Bahana Mandiri Bekasi, in semester two of academic year 2011/2012. Data needed is obtain from direct and indirect observation and collaboration. In the direct observation, the data is from field observation. In the indirect one, the data is from the test result. Meanwhile in collaboration, the collaborator informs teaching and learning process through choral drill technique. Based on the data collected it is found that some students are active in pronunciation practice through choral drill technique. Further, the students have more desire and motivation to improve their pronunciation skill. Looking up the evaluation table, the pronunciation from twenty one students in three cycles can be explained; in the first cycle, there are only three students (15%) who achieve the standard of minimum score. In the second cycle, there are nine students (45%) who achieved the standard minimum score. While in the third cycle, all of them (100%) can achieve the standard minimum score. Furthermore, the writer concludes that the use of choral drill technique can be one of the appropriate approach to teach English pronunciation for the students